Medicinal plant diversity and vegetation analysis of logged over hill forest of Tekai Tembeling Forest Reserve, Jerantut, Pahang - Eswani, Norhajar; Abd. Kudus, Kamziah; Salleh @ Japri, Mohd Nazre; Abd. Ghani, Awang Noor; Ali, M. (Canadian Center of Science and Education, 2010)
The study was carried out to analyze the species diversity and study of quantitative analysis of medicinal plants in logged over forest in Tekai Tembeling Forest Rese rve (TTFR). Four plots of 1-hectare size each were established within the forest area. A total of 6788 individual medicinal trees and non trees representing 231 species, 179 genera and 87 families were recorded. Th e species area curve did not approach an asymptote condition. The regression equation to estimate species richness was with r 2 =0.95%. The most diverse species for trees was Cinnamomum porrectum and Lygodium circinnatum for non trees. The most diverse plot was plot 2 with 7335 individuals and 188 species. Since the forest area was diverse in medicinal species, it is necessary to begin conservation assessment that will improve medicinal plants biodiversity.